Ectopic Cerebellar Cell Migration Causes Maldevelopment of Purkinje Cells and Abnormal Motor Behaviour in Cxcr4 Null Mice - Huang, Guo-Jen (Public Library of Science, 2014)
SDF-1/CXCR4 signalling plays an important role in neuronal cell migration and brain development. However, the impact of CXCR4 deficiency in the postnatal mouse brain is still poorly understood. Here, we demonstrate the importance of CXCR4 on cerebellar development and motor behaviour by conditional inactivation of Cxcr4 in the central nervous system. We found CXCR4 plays a key role in cerebellar development. Its loss leads to defects in Purkinje cell dentritogenesis and axonal projection in vivo but not in cell culture. Transcriptome analysis revealed the most significantly affected pathways in the Cxcr4 deficient developing cerebellum are involved in extra cellular matrix receptor interactions and focal adhesion. Consistent with functional impairment of the cerebellum, Cxcr4 knockout mice have poor coordination and balance performance in skilled motor tests. Together, these results suggest ectopic the migration of granule cells impairs development of Purkinje cells, causes gross cerebellar anatomical disruption and leads to behavioural motor defects in Cxcr4 null mice.